2005
DOI: 10.1177/000992280504400804
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in Defecation in Infants with Gastroesophageal Reflux Treated with Smaller Volume Feeds Thickened with Rice Cereal

Abstract: We prospectively evaluated the incidence of difficulty in defecation in infants with gastroesophageal reflux who were treated with smaller volume feeds thickened with rice cereal and also assessed the effect of changing the cereal to oatmeal. We evaluated 53 thriving infants with uncomplicated gastroesophageal reflux who were treated with smaller volume feeds thickened with rice cereal. Parents maintained records of bowel movements for 7 days. Rice was substituted by oatmeal cereal in those infants developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, improvement in per os tolerance or discontinuation based on parents decision cannot be excluded. Mascarenhas et al ( 18 ) have reported a rate of constipation of only 20% in infants receiving rice cereal for thickening. Our data show a decrease in the use milk thickener over the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, improvement in per os tolerance or discontinuation based on parents decision cannot be excluded. Mascarenhas et al ( 18 ) have reported a rate of constipation of only 20% in infants receiving rice cereal for thickening. Our data show a decrease in the use milk thickener over the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is high variability in feed‐thickening practices, and consequences of thickeners are numerous and may include NEC, hypernatremia, malabsorption of nutrients, constipation, dehydration, delayed GI transit, fatigue from nipple extraction, difficulty extracting liquid, decreased oral intake, or prolonged transition of oral feeding in the presence of oropharyngeal dysphagia . In addition, each 1 tsp/oz rice cereal or oatmeal adds 5 kcal/oz, and this increased energy density alters metabolism, which can lead to excessive body fat deposits …”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is high variability in feed-thickening practices, and consequences of thickeners are numerous and may include NEC, hypernatremia, malabsorption of nutrients, constipation, dehydration, delayed GI transit, fatigue from nipple extraction, difficulty extracting liquid, decreased oral intake, or prolonged transition of oral feeding in the presence of oropharyngeal dysphagia. 1,6,19,[22][23][24][25][26][27][28][29][30][31][34][35][36][37][38] In addition, each 1 tsp/oz rice cereal or oatmeal adds 5 kcal/oz, and this increased energy density alters metabolism, which can lead to excessive body fat deposits. 19,39 Thickeners are frequently used to treat dysphagia with the assumption that thickening decreases the flow rate, thus increasing oropharyngeal transit time to improve airway protection and oromotor control.…”
Section: Consequences Of Thickening For Dysphagia or Gastroesophagealmentioning
confidence: 99%
“…Moreover, thickening human milk is ineffective in reducing gastroesophageal reflux because the amylase in human milk will break down rice starch. 15,16 As the deprescription limits or end-use of added rice formula is not clear, other concerns of use are reported instances of excessive weight gain, irritability from rice intolerance or maldigestion, constipation, and necrotizing enterocolitis (NEC) in premature infants; [17][18][19][20][21][22] arsenic exposure has also been reported. 6,23 However, some reported benefits have been reductions in regurgitation and emesis, along with choke-gag-cough symptoms.…”
Section: Introductionmentioning
confidence: 99%